Phase segregation in manganese perovskites - Radaelli, P; Argyriou, D; Cox, D; Capogna, L; Casalta, H; Andersen, K; Cheong, S; Mitchell, J; Marezio, M (Materials Research Society, 1999)
The structural, magnetic and transport phase diagrams of the manganese perovskites (A 1-xA' xMnO 3) are characterized by several phenomena, including high-temperature polaronic behavior, charge-orbital and magnetic ordering and colossal magnetoresistance (CMR). These properties can be tuned by changing the doping level, the electronic bandwidth, and the A-site disorder. To demonstrate this, the recent x-ray synchrotron and neutron diffraction data on the crystallographic and magnetic modulation in La 0.33Ca 0.67MnO 3 are presented.